Teaching social studies in elementary and middle school - Joyce, William W. (Holt, Rinehart and Winston, 1979)
The textbook consists of two interrelated parts. Elements of the social studies, focuses on the major decisions confronting a teacher of the social studies. Exemplars in methodology deals intensively with the methods and materials used in teaching the social studies.